x(x+6)=x+5

Simple and best practice solution for x(x+6)=x+5 equation. Check how easy it is, and learn it for the future. Our solution is simple, and easy to understand, so don`t hesitate to use it as a solution of your homework.

If it's not what You are looking for type in the equation solver your own equation and let us solve it.

Solution for x(x+6)=x+5 equation:



x(x+6)=x+5
We move all terms to the left:
x(x+6)-(x+5)=0
We multiply parentheses
x^2+6x-(x+5)=0
We get rid of parentheses
x^2+6x-x-5=0
We add all the numbers together, and all the variables
x^2+5x-5=0
a = 1; b = 5; c = -5;
Δ = b2-4ac
Δ = 52-4·1·(-5)
Δ = 45
The delta value is higher than zero, so the equation has two solutions
We use following formulas to calculate our solutions:
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}$
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}$

The end solution:
$\sqrt{\Delta}=\sqrt{45}=\sqrt{9*5}=\sqrt{9}*\sqrt{5}=3\sqrt{5}$
$x_{1}=\frac{-b-\sqrt{\Delta}}{2a}=\frac{-(5)-3\sqrt{5}}{2*1}=\frac{-5-3\sqrt{5}}{2} $
$x_{2}=\frac{-b+\sqrt{\Delta}}{2a}=\frac{-(5)+3\sqrt{5}}{2*1}=\frac{-5+3\sqrt{5}}{2} $

See similar equations:

| F(x)=2x^2-9x+6 | | xx+6=x+5 | | 16t2-40t+25=0 | | 4+2x+4x=10 | | 6+8x-3x=61 | | 19^3-12x^2+16x=0 | | -7x+2)-3)=4 | | 18x-5=6x-(x+2)+(x+2) | | 2(x-5)=5(2x+1)+1 | | -14=3y+7 | | 12{3+a}=48 | | 3=9–3f | | b^2=41 | | 5/6x+9=4 | | 38-7x=-4(8x+3) | | 22=8u+6(u+2) | | 4x+8=6(x-1)-2x | | 8.8+z=19.4 | | Y=1/3x-19 | | u-3+ -4= -2 | | 24-8a=-8(a-2) | | 8+2x-1=128x-3 | | 2/5(3-m)-1/2(4-3m)=1/10(6m+17) | | -6+-2w=-10 | | 2(x^2-3x+4)+6x=8 | | x*(5/4)=6 | | 253x=125x-1 | | -1/8x=18. | | -19=x/18 | | x(3x+2)-3(x^2+x+5)=0 | | 10x+1=1002 | | 28+x=(30+x)0.95 |

Equations solver categories